Analysis Of Treatment Of Hemodialysis Patients at RSAU dr. M. Salamun - Anisa Rahmasari; Supriyadi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
Hemodialysis (HD) is a kidney replacement therapy that uses a special tool with the aim of treating symptoms and signs due to a low glomerular filtration rate so that it is expected to extend life and improve the quality of life of patients. The purpose of this study was to find out how hemodialysis patients at RSAU are treated. dr. M. Salamun. The research design used is descriptive with a survey research type. The population of this study were Hemodialysis medical personnel and kidney failure patients undergoing Hemodialysis at RSAU dr. M. Salamun. The sample size is 11 respondents (one medical staff and ten Hemodialysis patients). Data collection is done by interview process. Based on the results of research conducted on ten respondents regarding the treatment of Hemodialysis patients, it shows that the treatment and services provided by the Hemodialysis unit for Hemodialysis patients are very good.